Sustainable Crop Disease Management Using Natural Products 2015
DOI: 10.1079/9781780643236.0265
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly management of mycotoxigenic fungi and mycotoxin contamination.

Abstract: This chapter focuses on the incidence of mycotoxins in food and feeds and their health hazards, management of mycotoxins, decontamination and detoxification methods, biological methods of mycotoxin control and regulatory measures for the control of mycotoxin contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The radiation treatment includes UV rays, IR radiation, gamma rays, microwaves, sometimes electron beam radiation, pulsed light, and solar radiation. Surekha et al (2015) demonstrated an effective reduction in AF contamination levels in seeds treated with IR and UV radiation. UV treatment is mostly limited to the cereals industry and has been demonstrated for its promising results in lowering the AF levels (Ghanghro et al, 2016;Mir et al, 2021).…”
Section: Physical Detoxificationmentioning
confidence: 94%
See 1 more Smart Citation
“…The radiation treatment includes UV rays, IR radiation, gamma rays, microwaves, sometimes electron beam radiation, pulsed light, and solar radiation. Surekha et al (2015) demonstrated an effective reduction in AF contamination levels in seeds treated with IR and UV radiation. UV treatment is mostly limited to the cereals industry and has been demonstrated for its promising results in lowering the AF levels (Ghanghro et al, 2016;Mir et al, 2021).…”
Section: Physical Detoxificationmentioning
confidence: 94%
“…Surekha et al. (2015) demonstrated an effective reduction in AF contamination levels in seeds treated with IR and UV radiation. UV treatment is mostly limited to the cereals industry and has been demonstrated for its promising results in lowering the AF levels (Ghanghro et al., 2016; Mir et al., 2021).…”
Section: Prevention and Mitigation Of Aflatoxinsmentioning
confidence: 99%